Effective strategies for encouraging behavior change in people with diabetes. (November 2015) - Hood, Korey K; Hilliard, Marisa; Piatt, Gretchen; Ievers-Landis, Carolyn E
Behavioral management of diabetes leads to better health outcomes. This paper reviews the available literature on facilitators of behavior change in people with diabetes and highlights approaches and strategies diabetes care providers can utilize. The research and clinical evidence points to the critical nature of considering the content and structure of recommendations, and utilizing problem solving and teamwork approaches. Furthermore, close attention to individual and community factors will optimize behavior change. These factors include health literacy, community infrastructure, support within the family, and whether there are co-occurring eating and mood issues. Recommendations are provided to optimize communication and embed behavior change approaches in clinical and community encounters.